Analisis Faktor Pendapatan Penduduk di Indonesia - Lasta, Gracy Adira; Putra, Satria Yudha Ananta; Ghaisani, Armara Hanania (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2022)
There have been many developments in the global economy, especially in the investment sector. Among them is the increase in cross-border capital flows. Efforts are being made by the Indonesian government to increase cross-border capital flows, namely through increasing Foreign Direct Investment (FDI) and widening trade flows. Direct investment (FDI) and foreign relations are considered sources of cross-border capital flows that countries use to promote economic growth. This discussion will focus on how FDI and the impact of trade on the income of the Indonesian population during the period 2009 to 2020. The OECD (Organization for Economic Co-operation and Development) has also recommended three policies for Indonesia to focus on attracting more FDI to boost its economic growth. This study uses a quantitative descriptive method, with Multiple Linear Regression Test and Classical Assumption Test approaches to measure the relationship between variables. The results of this study indicate that there is a positive relationship between foreign direct investment and trade on the income of the population in Indonesia.